SEROSURVEILLANCE OF AVIAN INFLUENZA VIRUS SUBTYPE H5N1 WITH HAEMAGGLUTINATION-INHIBITION ON WILD AQUATIC BIRDS IN PULAU DUA SERANG NATURAL RESERVES, BANTEN PROVINCE - Elfidasari, Dewi; Solihin, Dedy Duryadi; Soejoedono, Retno Damayanti; Murtini, Sri; Noor, Yus Rusila (Makara Journal of Science, 2011)
Further detailed research is required to obtain deeper information on the role of wild birds on the distribution of Avian influenza in Asia. A research has been carried out on February–June 2007 focused on blood sampling (serosurveillance) of wild birds in Pulau Dua Nature Reserves (CAPD), Serang, Banten. The research is aimed to investigate the infection of AI virus sub-tye H5N1 on the studied wild birds. The blood samples were taken from studied aquatic birds, followed by HI (haemagglutination-inhibition) test. A total of 183 samples represent 7 water bird species were taken i.e Cattle egret Bubulcus ibis, Javan pond-heron Ardeola speciosa, Little egret Egretta garzetta, Intermediate egret Egretta intermedia, Black-crowned night heron Nycticorax nycticorax, Great egret Casmerodius albus and Grey heron Ardea cinerea. The result revealed that 41 (23.27%) samples showed the present of AIV antibodies serotype H5N1 which is identified as positive. Data showed 5 positive-test species, including B. ibis (29.27%), E. garzetta (29.27%), E. intermedia (4.88%), Ardeola speciosa (7.32%), and N. nycticorax (29.27%). A total of 41.46% were infected adult individual, whereas 58.54% were juveniles.